FORMULATION AND PHARMACOKINETIC DETERMINATION OF GALLIC ACID IN EMBLICA OFFICINALIS - S., Sangeetha; Samanta, Malay K.; R., Kavitha; N., Remya P.; S., Saraswathi T. (International Journal of Applied Pharmaceutics, 2017)
Objective: The present work was to formulate oral herbal tablets of Emblica officinalis extract and also with pure gallic acid, further to determine the dosage frequency through pharmacokinetic profiles obtained for the same. Methods: The Emblica officinalis fruits were suitably extracted and the concentration of gallic acid in Emblica officinalis extract was estimated by HPTLC (High-Performance Thin Layer Chromatography) with a comparison to pure form. Tablets were prepared with extract and synthetic form through direct compression technique by varying the process and formulation parameters. The formulated tablets were administered to rabbit models and their pharmacokinetic profile was studied after withdrawing blood samples through HPLC (High-Performance Liquid Chromatography). Results: The concentration of gallic acid in Emblica officinalis was found to be 8.21%. The pre and post compression parameters evaluated for the formulated batches found to be within the pharmacopoeial limits. The in vivo pharmacokinetic studies conducted in rabbit models showed that there were no significant differences with p-value between the pharmacokinetic data obtained for pure and extract gallic acid tablets. The Cmax was found to be 4.59±0.95 µg/ml in the extract form which was little low when compared to the pure form of 6.38±1.08 µg/ml. The t1/2 in the extract form was 6.0±0.33 h, whereas it was 4.92±0.36 h in the pure form of gallic acid. Conclusion: The Emblica officinalis extract tablet showed average t1/2 of 6 h, so about every 6 h one tablet compared to 4 h of t1/2 for pure gallic acid tablet can be the dosing frequency for the rabbit.